Phyllostachyos Caulis in Taeniam extract stimulates longitudinal bone growth via IGF-1 and JAK2/STAT5 signaling in rats - Yongwun An; Hee Woo Lee; Yun Chan Jung; Hyun Jae Woo; Younghoon Kim; Hohyun Kim; Yong Joon Jeong; A. M. Abd EI-Aty; Ji Hoon Jeong (PLoS ONE, 2025)
Longitudinal bone growth, which is regulated by endocrine and paracrine factors, is a critical determinant of linear growth during childhood. This study investigated the effects of an aqueous extract of Phyllostachyos Caulis in Taeniam (PCE) on longitudinal bone growth and its regulatory effects on circulating insulin-like growth factor-1 (IGF-1) in rats. Twenty-eight adolescent rats were randomly assigned to four groups (n = 7 per group): control, recombinant human growth hormone (rhGH) 20 μg/kg, PCE 200 mg/kg, and 400 mg/kg. After 10 days of administration, the serum levels of growth hormone (GH), IGF-1, IGF binding protein 3 (IGFBP3), and osteocalcin, as well as tibial length, were measured. In addition, the mRNA expression levels of IGF-1 and IGFBP3 in liver tissue were quantified via real-time polymerase chain reaction (qRT-PCR), and the protein expression levels of Janus kinase 2 (JAK2), signal transducer and activator of transcription 5 (STAT5), and IGF-1 were assessed via western blotting. Compared with the control, 400 mg/kg PCE significantly increased the serum levels of GH, IGF-1, IGFBP3, and osteocalcin in rats by 486.6%, 73.7%, 22.5%, and 27.8%, respectively (P < 0.01), and increased the tibial length by 7.4% (P < 0.01). Compared with the control, 400 mg/kg PCE also increased the mRNA expression of IGF-1 and IGFBP3 in the liver by 5.2-fold (P < 0.01) and 7.3-fold (P < 0.05), respectively. Moreover, compared with the control, 400 mg/kg PCE increased hepatic IGF-1 protein expression by 2.76-fold (P < 0.01) and promoted the phosphorylation of JAK2 and STAT5 by 1.13-fold (P < 0.05) and 2.82-fold (P < 0.01), respectively. These findings suggest that PCE promotes longitudinal bone growth in rats, potentially through GH-mediated IGF-1 regulation via the JAK2/STAT5 pathway.